A role for GAT-1 in Presynaptic GABA Homeostasis? - Conti, Fiorenzo; Melone, Marcello; Fattorini, Giorgia; Bragina, Luca; Ciappelloni, Silvia (Frontiers in Cellular Neuroscience, 2011)
In monoamine-releasing terminals, neurotransmitter transporters – in addition to terminating synaptic transmission by clearing released transmitters from the extracellular space - are the primary mechanism for replenishing transmitter stores and thus regulate presynaptic homeostasis. Here, we analyze whether GAT-1, the main plasma membrane GABA transporter, plays a similar role in GABAergic terminals. Re-examination of existing literature and recent data gathered in our laboratory show that GABA homeostasis in GABAergic terminals is dominated by the activity of the GABA synthesizing enzyme and that GAT-1-mediated GABA transport contributes to cytosolic GABA levels. However, analysis of GAT-1 KO, besides demonstrating the effects of reduced clearance, reveals the existence of changes compatible with an impaired presynaptic function, as mIPSCs frequency is reduced by one third and GADs and PAG levels are significantly up-regulated. Although the changes observed are less robust than those reported in mice with impaired dopamine, noradrenaline and serotonin plasma membrane transporters, they suggest that in GABAergic terminals GAT-1 impacts on presynaptic GABA homeostasis, and may contribute to the activity-dependent regulation of inh